WEB-BASED NAVIGATION AND ATTRACTION INFORMATION SYSTEM FOR TOURISTS IN DUNIA FANTASI AMUSEMENT PARK - Veony Virginia Suwardi; hadi Suprayitno (President University, 2022)
Amusement Park is the perfect destination forall-ages with plenty of attractions for both families and thrill-seekers. To accommodate the various attractions, the park builtmust be huge. Because of those, the tourist may struggle to selectan attraction to ride, waiting hours in a long queue line, andgetting overwhelmed by exploring the enormous park. Everyamusement park all over the world is experiencing this issue,including Dunia Fantasi. This final project development aim tobuild an information system that amusement park tourists, inthis case, Dunia Fantasi, could use while touring the park. Theproject presents a tourist information system with a navigationsystem and queue line management system to help tourist enjoytheir experience in Dunia Fantasi to the fullest. In addition, theDunia Fantasi management will also benefited from bettercustomer satisfaction. The system will consist of attractionsdescription, estimated waiting time, Dufan map, the number ofcapacity available, and which attraction are available to ride.